THE CORRELATIONS BETWEEN THERAPEUTIC COMMUNICATION AND ANXIETY LEVELS OF PATIENTS' FAMILIES IN FACING INVASIVE ACTIONS IN THE INPATIENT ROOM OF THE BEKASI REGENCY GENERAL HOSPITAL - Gurning, Risma Ayu; Deniati , Kiki; Meliyana, Ernauli (Jurnal Medicare, 2022)
This study discusses therapeutic communication with the patient's family anxiety level. Therapeutic communication is a problem that needs to be considered by health workers. Because, therapeutic communication is a very effective means to facilitate nurses in carrying out their roles and functions properly, so that the goals of nursing actions are optimally achieved. The research method used is quantitative with a cross sectional approach and purposive sampling. The population in this study was the patient's family, which amounted to 192 patients' families. With the results of the study showing the P value of 0.000, it can be concluded that p value (0.000) < value (0.05). This shows that there is a relationship between therapeutic communication and the level of anxiety of the patient's family in dealing with invasive actions in the Inpatient Room of the Bekasi Regency General Hospital.